2021
DOI: 10.1002/etc.5238
|View full text |Cite
|
Sign up to set email alerts
|

Species‐ and Tissue‐Specific Chronic Toxicity Values for Northern Bobwhite Quail (Colinus virginianus) Exposed to Perfluorohexane Sulfonic Acid and a Binary Mixture of Perfluorooctane Sulfonic Acid and Perfluorohexane Sulfonic Acid

Abstract: Per-and polyfluoroalkyl substances (PFAS) are globally distributed and present in nearly every environmental compartment. Characterizing the chronic toxicity of individual PFAS compounds and mixtures is necessary because many have been reported to cause adverse health effects. To derive toxicity reference values (TRVs) and conduct ecotoxicological risk assessments (ERAs) of PFAS-contaminated ecosystems for wildlife, species-specific PFAS chronic toxicity values (CTVs) are needed. The present study quantified P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Conversely, Menger et al [ 35 ] observed only reduced toxicity in zebrafish embryos exposed to a mixture of nine PFAS compared to individual PFAS. There are few PFAS mixture studies utilizing fish, but even in non-fish models, such as the American bullfrog ( Rana catesbeiana ) [ 33 ], Northern leopard frog ( Rana pipiens ) [ 34 ], mouse ( Mus musculus ) [ 36 ], and Northern bobwhite quail ( Colinus virginianus ) [ 37 , 38 , 39 ], there are no clear patterns of antagonistic, additive, or synergistic effects of PFAS mixtures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Menger et al [ 35 ] observed only reduced toxicity in zebrafish embryos exposed to a mixture of nine PFAS compared to individual PFAS. There are few PFAS mixture studies utilizing fish, but even in non-fish models, such as the American bullfrog ( Rana catesbeiana ) [ 33 ], Northern leopard frog ( Rana pipiens ) [ 34 ], mouse ( Mus musculus ) [ 36 ], and Northern bobwhite quail ( Colinus virginianus ) [ 37 , 38 , 39 ], there are no clear patterns of antagonistic, additive, or synergistic effects of PFAS mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression of the same enzyme can either be upregulated or downregulated depending on the PFAS compound or species [ 7 ]. While there is a limited number of PFAS mixture studies conducted in saltwater fish, many other freshwater fish and non-fish species have been used to assess PFAS mixture toxicities, although there is no clear trend towards additive, synergistic, or antagonistic effects [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. To reduce uncertainty in PFAS risk assessments, it is pertinent to better understand the effects of PFAS as mixtures and how selected components can affect toxicity.…”
Section: Introductionmentioning
confidence: 99%